Anti-IgE treatment with oral immunotherapy in multifood allergic participants: a double-blind, randomised, controlled trial. (February 2018) - Andorf, Sandra; Purington, Natasha; Block, Whitney M; Long, Andrew J; Tupa, Dana; Brittain, Erica; Rudman Spergel, Amanda; Desai, Manisha; Galli, Stephen J; Nadeau, Kari C; Chinthrajah, R Sharon
Summary: Background: Despite progress in single food oral immunotherapy, there is little evidence concerning the safety and efficacy of treating individuals with multiple food (multifood) allergies. We did a pilot study testing whether anti-IgE (omalizumab) combined with multifood oral immunotherapy benefited multifood allergic patients. Methods: We did a blinded, phase 2 clinical trial at Stanford University. We enrolled participants, aged 4–15 years, with multifood allergies validated by double-blind, placebo-controlled food challenges to their offending foods. Inclusion criteria included a positive skin prick test of 6 mm or more (wheal diameter, above the negative control), a food-specific serum IgE concentration of more than 4 kU/L for each food, or both, and a positive double-blind, placebo-controlled food challenge at 500 mg or less of food protein. Exclusion criteria included eosinophilic oesophagitis and severe asthma. Participants were randomised (3:1) with a block size of four, to receive multifood oral immunotherapy to two to five foods, together with omalizumab (n=36) or placebo (n=12). 12 individuals who fulfilled the same inclusion and exclusion criteria were included as controls. These individuals were not randomised and received neither omalizumab nor oral immunotherapy. Omalizumab or placebo was administered subcutaneously for 16 weeks, with oral immunotherapy starting at week 8, and was stopped 20 weeks before the exit double-blind, placebo-controlled food challenge at week 36. The primary endpoint was the proportion of participants who passed double-blind, placebo-controlled food challenges to at least two of their offending foods. This completed trial is registered withClinicalTrials.gov, numberNCT02643862 . Findings: Between March 25, 2015, and Aug 18, 2016, 165 participants were assessed for eligibility, of whom 84 did not meet the inclusion criteria and 21 declined to participate. We enrolled and randomised 48 eligible participants and the remaining 12 patients were included as nonrandomised, untreated controls. At week 36, a significantly greater proportion of the omalizumab-treated (30 [83%] of 36) versus placebo (four [33%] of 12) participants passed double-blind, placebo-controlled food challenges to 2 g protein for two or more of their offending foods (odds ratio 10·0, 95% CI 1·8–58·3, p=0·0044). All participants completed the study. There were no serious or severe (grade 3 or worse) adverse events. Participants in the omalizumab group had a significantly lower median per-participant percentage of oral immunotherapy doses associated with any adverse events (27% vs 68%; p=0·0082). The most common adverse events in both groups were gastrointestinal events. Interpretation: In multifood allergic patients, omalizumab improves the efficacy of multifood oral immunotherapy and enables safe and rapid desensitisation. Funding: US National Institutes of Health (NIH).